Analisis Pelaksanaan Tugas Pegawai Subbagian Kepegawaian Pada Dinas Tenaga Kerja Dan Transmigrasi Kota Dumai - Dina Putri Utami; Sofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Dina Putri Utami (0701120080) Implementation Task Analysis Employee Subdivision Officer at the Office ofManpower and Transmigration Dumai, led by Dra. Sofia Achnes, M.Sc.The determination of the duties and functions of each unit of work that is within the District / City Governmentestablished by the Regent / Mayor of No. 15 of 2006, concerning the duties, functions and job descriptions as theexecutive element of the local government. Implementation of employee duties is a responsibility of an employee inorder to achieve success implementing a work activity that can take place efficiently and effectively, which isnecessary to arrange for the achievement of harmony and harmony of all parties directly involved in the execution ofa job.At the beginning of the study the authors assume that there are some things that can not be implemented properlyand the maximum first, to prepare the collection and processing of data and information relating to office personneland formation. Second, conduct inventories of staffing problems and troubleshooting tips for the preparation ofmaterials, preparation of materials and third Conduct data collection personnel.Based on the phenomena encountered in the field, the research problem is formulated How Subdivision EmployeeTask Analysis Implementation Officer at the Office of Manpower and Transmigration Dumai and factors thatinfluence the implementation of Employee Duty Subdivision Officer at the Office of Manpower and TransmigrationDumai.This research uses quantitative research, and analyze the collected data used descriptive method. Researchers aretrying to reveal the facts in accordance with the fact that there is no intervention for the condition occurs. Datacollection techniques in this study observation and questionnaires. Who responded to the study is the Head office,Secretary, Chief Subdivision, Chief, Section Chief, Staff, Pengadministrasi General, and Administrative Staff.